KONSTRIBUSI OSIS DALAM MEMBENTUK KARAKTER TEMAN SEBAYA - Muhajir (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2021)
The OSIS supervisor is usually appointed by the school to assist the OSIS management in carrying out their duties and the principal is the main person in charge of OSIS activities. In terms of funding, all OSIS activities are funded from the School Revenue and Expenditure Budget (APBS). Sometimes in the field, OSIS activities often experience obstacles, for example the emergence of violations committed by OSIS administrators who are not orderly when participating in routine coaching. As for the title of this research is